Pilot test to assess the translated and culturally adapted versions into Colombian Spanish of the KOOS-JR, KOOS-12, HOOS-JR and HOOS-12 questionnaires - Lugo-Agudelo, Luz Helena; Aguirre-Acevedo, Daniel Camilo; Moore, José Luis; Rada, Carlos; Spir, María Alejandra; Velásquez, Juan Carlos; Medina, Alejandra; Valderrama-Molina, Carlos Oliver (Revista Colombiana de Ortopedia y Traumatología, 2024)
Introduction: Assessing the symptoms and impact of knee osteoarthritis (KOA) and hip osteoarthritis (HOA) on functional capacity and quality of life is paramount to determine the effectiveness of treatment and improve clinical outcomes. Objectives: To describe the translation and cultural adaptation process into Colombian Spanish of the KOOS-12, KOOS-JR, HOOS-12, and HOOS-JR questionnaires; to present the results of their use in a pilot test carried out to evaluate the understanding of the items; and to report the results obtained in these versions by patients with KOA and HOA in terms of functionality, pain, and quality of life. Methodology: Descriptive study. We first describe the translation and adaptation process into Colombian Spanish of the KOOS-12, HOOS-12, KOOS-JR, and HOOS-JR questionnaires. Then, the results of a pilot test in which the Colombian Spanish versions of these questionnaires were administered to 55 patients with KOA (n=37) and HOA (n=18) are reported. Spearman's correlation coefficient (rho) was used to evaluate the correlations between the scores obtained with these instruments (global and domain scores) and the scores obtained using the Visual Analog Scale (VAS) and the SF-36 health survey domains. Results: The overall scores on the KOOS-12, KOOS-JR, HOOS-12, and HOOS-JR were 42.7, 46.5, 39.6, and 38.3, respectively. In the case of the KOOS-12 and HOOS-12 questionnaires, the score in each of their domains (pain, function in activities of daily living, and quality of life) never exceeded 50 points. Regarding the correlations between the scores obtained in the SF36 survey domains and the scores obtained in the four questionnaires, it was observed that they were very weak-weak relative to the total KOOS-12 score (rho= 0.2-0. 4), with the exception of the social function domain (rho= 0.5); very weak-weak for the KOOS-JR score (rho= 0.1-0.4); moderate-strong (rho= 0.5-0.8) for the HOOS-12 total score, with the exception of the vitality dimension (rho= 0.3); and very weak, weak, moderate, and strong for the HOOS-JR score. Conclusion: According to the results of the pilot test, it can be stated that the versions translated and adapted into Colombian Spanish of the KOOS-12, HOOS-12, KOOS-JR, and HOOS-JR questionnaires presented here could be used to evaluate the impact of KOA and HOA in the country in terms of pain, function in activities of daily living, and quality of life. However, their validation process needs to be completed.